Doxorubicin-Loaded Iron Oxide Nanoparticles Induce Oxidative Stress and Cell Cycle Arrest in Breast Cancer Cells - Elisa Parcero Hernandes; Danielle Lazarin-Bidóia; Raquel Dosciatti Bini; Celso Vataru Nakamura; Luiz Fernando Cótica; Sueli de Oliveira Silva Lautenschlager (MDPI AG, 2023)
Cancer is one of the most common diseases nowadays and derives from the uncontrollable growth of a single cell. Magnetic nanoparticles (NpMag) offer various possibilities for use in the biomedical area, including drug delivery mediated by magnetic fields. In the current study, we evaluated the in vitro effects of iron-oxide magnetic nanoparticles conjugated with the antitumor drug doxorubicin (Dox) on human breast cancer cells. Our results revealed that magnetic nanoparticles with Dox (NpMag+Dox) induce cellular redox imbalance in MCF-7 cells. We also demonstrate that iron-oxide nanoparticles functionalized with Dox induce oxidative stress evidenced by DNA damage, lipid peroxidation, cell membrane disruption, and loss of mitochondria potential. As a result, NpMag+Dox drives MCF-7 cells to stop the cell cycle and decrease cell migration. The association of NpMg+Dox induced a better delivery of Dox to MCF cells, mainly in the presence of a magnetic field, increasing the death of MCF cells which might reduce the toxicity for healthy cells providing a better efficacy for the treatment. Thus, iron-oxide nanoparticles and doxorubicin conjugated may be candidate for anticancer therapy.